profile
Опубликовано - 1 месяц назад | По предмету Математика | автор Аноним

Корень из(х2+8х+27)=корень из(х2+8х)+3

  1. Ответ
    Ответ дан Соколова Ксения
    √( х ^ 2 + 8 * х + 27 ) = √ (х ^ 2 + 8 * х ) + 3 ;
    √( х ^ 2 + 8 * х + 27 ) ^ 2 = ( √ (х ^ 2 + 8 * х ) + 3 ) ^ 2 ;
    х ^ 2 + 8 * х + 27 = (х ^ 2 + 8 * х ) + 2 * 3 * √ (х ^ 2 + 8 * х ) + 9 ;
    х ^ 2 + 8 * х + 27 = х ^ 2 + 8 * х + 6 * √ (х ^ 2 + 8 * х ) + 9 ;
    х ^ 2 + 8 * х + 27 - х ^ 2 - 8 * х - 9 = + 6 * √ (х ^ 2 + 8 * х ) ;
    + 8 * х + 27 - 8 * х - 9 = + 6 * √ (х ^ 2 + 8 * х ) ;
    18 = + 6 * √ (х ^ 2 + 8 * х ) ;
    3 = √ (х ^ 2 + 8 * х ) ;
    3 ^ = √ (х ^ 2 + 8 * х ) ^ 2;
    x ^ 2 + 8 * x - 9 = 0 ;
    Отсюда, х= - 9 и х = 1.
    0